Pengembangan Sumber Daya Manusia Berdasarkan Pengaruh Reward dan Motivasi Kerja Terhadap Produktivitas Kerja - Revansyah Valleri Akbar; Herudini Subariyanti (Journal of Trends Economics and Accounting Research, 2023)
The success of an organization is closely related to the quality of its human resources, because human resources have an important role as actors, drivers and determinants of organizational work results based on company operational activities, both in quality and quantity. In this case, there are often social disparities within the organization that result in the lack of effectiveness of employee performance. Therefore, to avoid this ineffectiveness, it is necessary to provide rewards and work motivation which is believed to be an instrument to achieve more optimal work productivity. This study aims to determine whether there is an effect of reward and work motivation on work productivity at PT XYZ, Jakarta. In this study, using an explanatory quantitative method approach and the sample obtained was 45 people using incidental sampling techniques. The data collection method in this study uses observation, interview, documentation and questionnaire techniques (questionnaires) and the data analysis technique method used, namely descriptive statistical analysis test using data instrument test, hypothesis testing, classical assumption test and multiple linear regression test. Data processing using the SPSS V25 software program. From the research that has been done, it shows the results that rewards and work motivation have a positive and significant effect on work productivity. This is evidenced by the results of hypothesis testing and multiple linear regression tests.